MultiChurch : exploring the future of multisite - House, Brad, 1976-; Allison, Gregg R. (Grand Rapids, Michigan : Zondervan, 2017)
"Is it time for your church to go multisite? It seems everybody is doing it these days, so how do you know if it is the right solution for your congregation? MultiChurch brings clarity to the multisite movement and assembles the lessons it has learned over the past fifteen years. It explores the opportunities presented by the various forms of multi-site church, identifies areas of concern, and concludes that multisite is not only a biblically sound ecclesiological model, but also a model that provides a compelling solution to contemporary reductionism in the church."--Publisher website.
Introduction -- A multichurch evolution -- Section 1: Scouting. Landscape -- Landmarks -- Landmines -- The future -- Section 2: Orienteering. MultiOrg -- MultiPolity -- MultiMinistry -- MultiMoney -- MultiMembership -- Section 3: Setting out. Navigating Transition -- The rest of the story -- Appendix I: Grievance Policy -- Appendix II: Micropolity.
Includes bibliographical references.
Keywords: Multi-site churches; Church development, New; Christian leadership; Church management